2013
DOI: 10.1111/1756-185x.12180
|View full text |Cite
|
Sign up to set email alerts
|

Isokinetic muscle performance of the hip and ankle muscles in women with fibromyalgia

Abstract: In the light of our results, we may conclude that muscle strength and muscle fatigue seem to decrease in FMS patients' both proximal and distal lower extremity muscles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…Additionally, they reported that the decreased muscle performance in FMS patients was not related with the clinical findings, including pain severity, number of tender points, and duration of the symptoms. Yetigin et al 20 compared FMS patients and controls with respect to proximal or distal muscle strength and muscle 20 To the best of our knowledge, we have studied wrist muscles of the upper extremity of FMS patients and shown that these patients had reduced isokinetic muscle strengths when compared with healthy subjects for the first time in the literature.…”
Section: Discussionmentioning
confidence: 98%
“…Additionally, they reported that the decreased muscle performance in FMS patients was not related with the clinical findings, including pain severity, number of tender points, and duration of the symptoms. Yetigin et al 20 compared FMS patients and controls with respect to proximal or distal muscle strength and muscle 20 To the best of our knowledge, we have studied wrist muscles of the upper extremity of FMS patients and shown that these patients had reduced isokinetic muscle strengths when compared with healthy subjects for the first time in the literature.…”
Section: Discussionmentioning
confidence: 98%
“…Although the etiology of FM remains unclear, many factors, including the dysfunction of the central and peripheral nervous system, immune and hormonal system, as well as psychological factors can contribute to FM. Abnormal central sensitization, reduced blood flow to muscles during exercise, increased muscle hypertonicity, localized muscle hypoxia, deposition of mucopolysaccharides within muscles, pathological alterations in the sympathetic system and glycolysis, and decreased ATP and phosphocreatine have been found to be related to FM [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Prolonged muscle tension and ischemia can cause painful symptoms in FM, which, in turn, leads to decreased muscle performance and physical capacity. Maximal isometric and isokinetic muscle performance of the upper and lower extremities has been evaluated in many studies [9][10][11][12][13][14][15][16][17][18][19]. Lower extremity muscles are the most evaluated parts of the body in patients with FM.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared to controls, patients with fibromyalgia have decreased muscle strength. [3][4][5] The history and physical examination are the basis for diagnosing and clinical follow-up of patients with fibromyalgia. In the interrogation, the visual analog pain scale is a simple resource for clinical studies.…”
mentioning
confidence: 99%